Pengembangan Media Pembelajaran Berbasis Komputer dengan Adobe Flash Pro CS6 pada Materi Luas Bangun Datar - Saputra, Rahmat; Thalia, Septyani; Gustiningsi, Tria (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
This study aims to produce learning media which valid and practical. The researcher uses design research type of development study with two stages, namely the preliminary stage and the prototyping stage. In the preliminary stage, the researcher analyzes the material in a flat shape and continues with making a flowchart to determine the order in which the material will be displayed on the learning media. At the prototyping stage, researcher use a formative evaluation flow consist of self evaluation, expert review, one-to-one, small group, and field tests. In this study, the flow carried out only reached the small group stage. Data were collected by walkthroughs, questionnaires, interviews, and test. The research subject is seventh graders of SMP IT Izzuddin Palembang. The result of this study is a learning media which produced is valid and practical. The validity of a learning media is shown from the results of validation at the expert review and one-to-one stages which state that learning media are good in terms of content, construct, and language. The practicality of a learning media is also seen at the small group stage that students can use learning media well, can help students understand the material, and students are interested in using it.